2019
DOI: 10.3390/jcm8101556
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Efficacy of the Bacille Calmette–Guérin Vaccination in Conjunction with First Line Antibiotics and Liposomal Glutathione

Abstract: Mycobacterium tuberculosis (M. tb) is the etiological agent that is responsible for causing tuberculosis (TB). Although every year M. tb infection affects millions of people worldwide, the only vaccine that is currently available is the Bacille Calmette–Guérin (BCG) vaccine. However, the BCG vaccine has varying efficacy. Additionally, the first line antibiotics administered to patients with active TB often cause severe complications and side effects. To improve upon the host response mechanism in containing M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…This measurement was used to investigate the efficacy of using 1/10 of the MIC of PZA and INH in controlling M. tb infection within in vitro granulomas inT2DM group, with the basis coming from a previous finding in our lab that showed MIC of PZA and INH was able to reduce M. tb . burden in healthy individuals ( Abrahem et al., 2019 ). However the efficacy of these antibiotics at 1/10 MIC against M.tb in individuals with T2DM was not previously determined.…”
Section: Resultsmentioning
confidence: 99%
“…This measurement was used to investigate the efficacy of using 1/10 of the MIC of PZA and INH in controlling M. tb infection within in vitro granulomas inT2DM group, with the basis coming from a previous finding in our lab that showed MIC of PZA and INH was able to reduce M. tb . burden in healthy individuals ( Abrahem et al., 2019 ). However the efficacy of these antibiotics at 1/10 MIC against M.tb in individuals with T2DM was not previously determined.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that autophagy functionally benefits some diseases such as cancer, cardiomyopathy, diabetes, liver disease, and infections ( 29 31 ). LC3B is a mammalian homolog of the yeast ATG8 protein, which is a ubiquitin-like protein related to autophagosomal membranes ( 32 , 33 ). Therefore, LC3B is an important and direct marker used for detecting autophagy levels ( 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…LC3B is a mammalian homolog of the yeast ATG8 protein, which is a ubiquitin-like protein related to autophagosomal membranes ( 32 , 33 ). Therefore, LC3B is an important and direct marker used for detecting autophagy levels ( 32 , 33 ). The LC3B protein in the granulomas were stained by an anti-LC3B antibody tagged with PE, a red fluorescent dye.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in vitro glutathione (GSH) treatment of immune cells isolated from Mycobacterium bovis Bacille Calmette-Guérin (BCG) vaccine subjects improves the immune response and clearance of the M. tb [ 65 ]. GSH treatment has been shown to increase production of the cytokines IFN-γ and TNF-α, resulting in enhanced effector functions of macrophages, natural killer cells, and CD8+ T-cells.…”
Section: Th1 Vs Th2 In Context Of Tb and Hivmentioning
confidence: 99%